If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2n + -15 = 61 Reorder the terms: -15 + -2n = 61 Solving -15 + -2n = 61 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '15' to each side of the equation. -15 + 15 + -2n = 61 + 15 Combine like terms: -15 + 15 = 0 0 + -2n = 61 + 15 -2n = 61 + 15 Combine like terms: 61 + 15 = 76 -2n = 76 Divide each side by '-2'. n = -38 Simplifying n = -38
| f(x)=x^2+5x-2(2f(2)) | | f(x)=x^2+5x-2 | | 6+10x=42 | | [2-5(6+11)]= | | -4x+9y=-27 | | -3v+32=-7v+2(1-3v) | | 5x+6y=-18 | | -7x-2y=52 | | 2x^2-2304=0 | | 3+10=80-4 | | 4x+6y=-26 | | (8x+2)-4=18 | | 331x+6=7 | | 13+5= | | 18q=-11 | | q+13=61 | | -5x+49=-8(x-8) | | 8x-110=2x-14 | | 3+2x=x-5 | | 11z^2=-18 | | s+9=37 | | 2+3m= | | b^2-4b-b+4= | | w-8=-2 | | Y=x^2+4x+8 | | 3x*(2x+5)-(x+3)*(3x-1)=1 | | 11z^2+54=36 | | 10x+80=100 | | (3*4)n-9n=39 | | 5.23-(-9.1)= | | X^2=8x-20 | | r^2+4r+6r+24= |